Case report: silicosis complicated by bronchial stones and tracheoesophageal fistula - Zhang Dong; Ma Lijie; Guo Bin; Yu Ke (The Egyptian Journal of Bronchology)
Abstract Silicosis is one of the most serious occupational respiratory diseases worldwide. This article reports a patient with a long history of cough and sputum production who ended up with bronchial stones and a tracheoesophageal fistula (TEF). This case emphasizes the importance of comprehensive assessment for patients with silicosis. Especially when atypical symptoms arise, bronchial stones and tracheoesophageal fistulas should be promptly identified to reduce misdiagnosis and missed diagnosis, thereby improving patient prognosis.